Improvement of Photostability in Formulation: A Review - R. Bhalekar, Mangesh; Harinarayana, Dommati; R. Madgulkar, Ashwini; J. Pandya, Shridhar; K. Jain, Devendra. (Asian Journal of Chemistry, 2010)
In this review an improvement of photostability in formulation is discussed the issue of photostability in pharmaceutical dosage forms. This review deals with mechanism of photodegradation with examples, factors affecting photostability, formulation characteristics affecting photostability, ICH guidelines for testing photostability of new drug substances and products. Various reported formulation approaches which improved photostability have also been discussed.